Old Data, Changed Times, New Resource? A Case Study, Barrytown, New Zealand, Ilmenite Garnet Gold Zircon. Issue 1 (1st December 2019) - Burlet, Luke; Lee, Graham
Summary: The project geology has been compiled reviewed and a new, modern, resource database has been developed for the Barrytown New Zealand, Ilmenite Garnet Gold Zircon project. The work required existing databases to be updated to include all historic mineral sands and gold data, and consolidated and checked versus original records. The NZ Petroleum and Minerals (NZPAM) Mineral Report (MR) documents for the Barrytown project were checked and the data was compared to that contained in the project databases compiled prior to this recent 2018 work. Additional information was extracted and added into the databases including omitted holes, collars, size fractions, magnetic fractions, lithology, and especially gold assays. Within the project budget, as much additional data as could possibly be extracted was found by being persistent and systematically working through the contained information. The NZPAM system, although not ideal, does contain a wealth of information.